Implementation of the Teaching Games for Understanding Learning Model in Soccer Learning at Junior High School - Jela Pediyani; Ramadhan Arifin; Kuncoro Darumoyo; Mashud (Jurnal Master Penjas & Olahraga, 2026)
This study aims to determine the effect of implementing the Teaching Games for Understanding (TGfU) on the soccer abilities and skills. The study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The study population consisted of 138 students at SMP Negeri 2 Tanta, while the sample comprised 20 eighth-grade A students selected using purposive sampling. The research instrument was a soccer skill test covering technical execution, ball control, teamwork, understanding of simple tactics, and attitude toward the game. Data analysis utilized descriptive statistics, a normality test, and a Paired Sample t-test. The results showed that the average pretest score of 10.30 increased to 14.95 on the posttest, with a significance value of 0.004 (p < 0.05). It was concluded that the TGfU method has a significant effect on improving students’ soccer abilities and skills.